Serbian Wine producers' performance evaluation: A netnographic baseline study of wine industry in Serbia - Valčić Uroš; Zarić Vlade (Ekonomika Poljoprivrede (1979), 2022)
The paper presents the wine production performance in the Republic of Serbia. The research adopts quantitative and qualitative methods, using a relatively novel method, netnography, which involves the observation and analysis of specific social groups or occurrences in the digital world using search engines as the primary source of data gathering. Key factors identified in the study are land, labor, capital and factors supply and demand. Goal of this research is, through the analysis of before mentioned factors, to evaluate wine production of Serbian wine producers. The paper also examines current conditions and possibilities of grape growing and wine making in the Republic of Serbia.